Ethanobotanical, phytochemical and pharmacological properties of Zizyphus nummularia (Burm. F.): A Review - Babita Aggarwal; Pankaj Sharma; HS Lamba (International Journal of Phytomedicine, 2018)
Zizyphus nummularia (Burm. F.), Family: Rhamnaceae, is widely distributed in dry regions of India. It is a bushy weed used as folk medicine. The plant is valued for its nutritional edible fruits. Traditionally, it is used in mental retardation, fever, diarrhea, dysentery. The plant has been evaluated for various pharmacological activities such as anti-inflammatory, anthelmintic, antibacterial, antifertility activity. Present review discusses phytochemistry and pharmacological aspects of the drug.